The Unfolding of the Sky - Krog, Antjie; Loots, Ronelle ((n/a), 1999)
"Landscape of Memory" volume 3. Soros Documentary Fund. Volume three of "Landscape of Memory," a four part documentary series on reconciliation in Southern Africa. The film centers on a dialogue between two women, an Afrikaner and an African. One has been a victim of the Apartheid system, the other has reported on the hearings of the Truth and Reconciliation Commission. Together they explore the notion of reconciliation, and what it means for each of them. Their shared journey into South Africa’s heart of darkness searches for truth and reconciliation in the country.